The GPS data processing strategies for the engineering structure monitoring scheme - Wan Mohd. Akib, Wan Abdul Aziz (2002)
Monitoring and detecting deformations within an engineered structure can be determined using a number of geodetic (precise) methods, e.g. geotechnical approach, terrestrial observations and spacebased methods. Nowadays, the GPS technology has become the most important tool for estimating the large structural engineering deformation such as buildings, dams, long span bridges, etc. In order to ensure that the engineering structures are exhibiting a safe deformation behavior, a repeated and/or continuous GPS measurements can be employed. The GPS technology provides a quick and precise method of determining 3D movements of a structure over time. Application of GPS technique of deformation detection on a high-rise building is one example of this approach. The appropriate processing strategies of GPS observable to estimate the geodetic parameters of interest is usually carried out in post processing mode, but one may ask ‘how does one really tell the quality of GPS solutions?’ Two types of adjustments can be used in GPS processing, e.g. minimal constraint and constraint adjustment.. This paper therefore highlights the processing strategies of the GPS data from two epoch observations for monitoring surveys - Case study: KOMTAR building, in Penang, Malaysia. The results of the adjustment in deformation surveys are presented and discussed.